2004
DOI: 10.1080/16501970410022426
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial differences as predictors for recovery from chronic low back pain following manipulation, stabilizing exercises and physician consultation or physician consultation alone

Abstract: We suggest that dysfunctional profile patients are more sensitive to respond even to treatment without any specific psychosocial elements. This should be considered when evaluating any treatment effects. Among dysfunctional profile patients, pain-related anxiety and decreased acceptance of pain may contribute to their sensitivity to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…We also stress the importance of implementing exercise programs to stabilize the lumbar spine (29). A study with 204 patients with chronic low back pain conducted by Riipinen et al has confirmed the positive effects of exercise in the treatment of pain and functional disability (30).…”
Section: Discussionmentioning
confidence: 97%
“…We also stress the importance of implementing exercise programs to stabilize the lumbar spine (29). A study with 204 patients with chronic low back pain conducted by Riipinen et al has confirmed the positive effects of exercise in the treatment of pain and functional disability (30).…”
Section: Discussionmentioning
confidence: 97%
“…Three of the five studies included31 32 52 used a CS method that incorporates the biopsychosocial model. Riipinen et al 31 and Vollenbroek-Hutten32 used the Multidimensional Pain Inventory (MPI) (see table 3) to subclassify.…”
Section: Discussionmentioning
confidence: 99%
“…Riipinen et al 31 and Vollenbroek-Hutten32 used the Multidimensional Pain Inventory (MPI) (see table 3) to subclassify. Previous studies have shown that using this multiaxial assessment gives more consistent results53 than studies using single aspects (physical, psychological or social) in combination 54 55.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations